Comparison of Quantamatrix Multiplexed Assay Platform and GenoType MTBDR Assay Using Smear-Positive Sputum Specimens From Patients With Multidrug- Resistant/Extensively Drug-Resistant Tuberculosis in South Korea - Kim, Seoyong; Kim, Yeun; Chang, Yunhee; Hirgo, Workneh Korma; Chang, Chulhun L.; Shim, Tae-sun; Uh, Young; Lee, Hyeyoung (Frontiers in Microbiology, 2019)
Rapid detection of drug-resistant tuberculosis (DR-TB) is crucial for timely treatment and management. The GenoType MTBDRplus and MTBDRsl (MTBDR) assays have been endorsed by the World Health Organization (WHO) for the detection of DR-TB. However, MTBDR assays cannot simultaneously detect multidrug-resistant TB (MDR-TB) and extensively drug-resistant TB (XDR-TB). Furthermore, interpretation of the MTBDR assay requires trained people, and the assay has low sample throughput, being able to process up to 12 samples in parallel. We have developed the Quantamatrix Multiplexed Assay Platform (QMAP) to detect MDR-/XDR-TB simultaneously. The interpretation of QMAP results is automated, and the platform can process up to 96 samples in parallel. To compare the performance of QMAP with MTBDR assays, we performed QMAP and the MTBDR assay on 76 smear-positive, Mycobacterium tuberculosis culture-positive sputum specimens. Compared with phenotypic drug susceptibility testing (DST) results, the sensitivity and specificity of QMAP were 100% and 98% for rifampin resistance, 80% and 100% for isoniazid resistance, 44.4% and 100% for ethambutol resistance, 100% and 100% for fluoroquinolone resistance, and 100% and 100% for second-line injectable drug resistance, respectively. The sensitivity and specificity of MTBDR assays were 100% and 98% for rifampin resistance, 80% and 100% for isoniazid resistance, 44.4% and 98.1% for ethambutol resistance, 100% and 100% for fluoroquinolone resistance, and 100% and 100% for second-line injectable drug resistance, respectively. The sensitivity and specificity of QMAP were 85.0% and 100%, respectively, for the detection of MDR-TB and 100% and 100%, respectively, for XDR-TB. The sensitivity and specificity of MTBDR assays was consistent with those of QMAP. Our study showed that the QMAP assay has sensitivity and specificity equivalent to that of MTBDR assays in smear-positive sputum specimens. In combination with phenotypic DST, QMAP might be useful as a supplementary DST assay for rapid detection of MDR-/XDR-TB.